The prevalence and impact of exposure to chronic violence among adolescents in Manenberg - Wynchank, Nadya Esther Julia Natasha (2000)
Bibliography: leaves 97-130.The aim of the present study is to investigate the prevalence and impact of adolescents' exposure to violence in Manenberg; a poor coloured dormitory suburb on the periphery of Cape Town. Three categories of violence are focused upon, namely, community violence, family violence and sexual violence. In addition, the nature and prevalence of both school and gang violence are established. The study determines the point prevalence of possible posttraumatic stress disorder (PTSD), and investigates the presence of additional distress symptoms consequent to violence exposure. Furthermore, socio-demographic characteristics as protective/risk factors are identified in relation to PTSD scores, Distress scores and Violence scores. Using a cross-sectional design, a self-report questionnaire was administered to all grade VIII pupils (N = 482) present at the three secondary schools in Manenberg, on three separate days, between 12-19 October 1999. The questionnaire consisted of the Harvard Trauma Questionnaire (HTQ), appropriately modified; trauma list and PTSD symptom list (Mollica, 1991), as well as an adaptation of the Checklist of Child Distress Symptoms (CCDS) (Martinez and Richters, 1993). A violence exposure list was devised to determine the source and nature of community, family and sexual violence experienced by subjects. Considering this was a pilot study, no second stage study was performed on screenpositives. Data were analysed using descriptive statistics as well as a multiple regression system named the Generalised Linear Model.The prevalence ofPTSD was estimated at 5.13% (n 24, x = 1.55, s 0.48). Of the total sample, 93.4% (n = 436) reported the presence of one or more PTSD symptoms consequent to exposure to trauma. Elevated PTSD and CCDS scores had a significant association with: females (p < 0.0071 and p < 0.0003 respectively) having a non-parent as a primary caretaker (p < 0.03 and p < 0.015, respectively), having Xhosa as a home language (p < 0.037 and p < 0.009 respectively), and having lived in numerous homes (p < 0.0082 and p < 0.004, respectively). In addition, elevated CCDS distress scores were associated with those subjects aged; 15 years (p < 0.014). PTSD scores were strongly associated with CCDS distress scores (r = 0.70), producing a coefficient of determination of 49.2%. Regarding exposure to violence, the vast majority of subjects 93.3% (n = 439) reported having personally experienced either community, family or sexual violence. And 18.5%(n = 86) had a personal experience of sexual violence (12.6% of males and 24% offemales).A further 79.7% (n = 367) of subjects reported having witnessed someone being shot or stabbed either in their home or in Manenberg and 20.9% have, themselves, been shot or stabbed. With CCDS distress symptoms, 31.38% (n 134) feel that life is not worth living and they wish they were dead and a further 15.3% (n = 68) report having attempted suicide